The Ideal Doctor Image in Asian Countries: A Qualitative Study of Gen Z Patient's Perspective - Ezra Yanuarista Rosa; Mohamad Syahriar Sugandi (Eduvest - Journal of Universal Studies, 2023)
Understanding the image of the ideal doctor from the patient's point of view is crucial for improving healthcare experiences, especially considering the phenomenon of patient dissatisfaction in Asian countries. This research adopts a multi-dimensional approach, incorporating symbolic interaction, cultural background, and communication theories to explore patients' perspectives on the ideal doctor. By examining the communication process through this lens, researchers can uncover the symbolic meanings attributed to doctors and their behaviours, shedding light on patients' perceptions of the ideal doctor. Then, by considering the cultural backgrounds among Asian countries, the research explores how cultural values, beliefs, and norms influence the image of the ideal doctor. This research is qualitative research, with an interpretive phenomenological approach. This research uses in-depth interviews, to gather patient views about the ideal doctor. To identify recurring themes and patterns, the collecting data will be coded using Atlas.it after that the result could be provide insight into the qualities, behaviours, and attributes that patients associate with the ideal doctor.